2002
DOI: 10.1007/s00240-002-0237-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different combined preservation modalities on warm ischemic kidneys: effect on oxidative stress, hydrostatic perfusion characteristics and tissue damage

Abstract: Hemodynamic disorders in brain dead organ donors induce hypoxia, warm ischemia and finally tissue damage. A cold preservation period also induces tissue and cellular lesions. The two major modes of preservation are cold storage (CS) and hypothermic pulsatile perfusion (HPP). We aimed to compare the influence of each mode of preservation and their combination on oxidative stress, perfusion characteristics and tissue damage, after a period of warm ischemia. Rat kidneys which had undergone ischemia (0, 30, 60 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Our findings on microtubule cold-stability have compelling clinical applications, such as prolonging the survival of organs awaiting transplantation (Maathuis et al, 2007; Niemann et al, 2015). Prolonged cold storage has been shown to induce mild oxidative stress to organs (Fabre et al, 2002). Therefore, the standard cold storage medium, UW solution, is enriched in antioxidant components.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on microtubule cold-stability have compelling clinical applications, such as prolonging the survival of organs awaiting transplantation (Maathuis et al, 2007; Niemann et al, 2015). Prolonged cold storage has been shown to induce mild oxidative stress to organs (Fabre et al, 2002). Therefore, the standard cold storage medium, UW solution, is enriched in antioxidant components.…”
Section: Discussionmentioning
confidence: 99%
“…Also, intrarenal resistance in the VSOP group was comparable to that in the controls, in contrast to intrarenal resistance in the OMP group, which increased during reperfusion. Previous studies also showed induction of oxidative stress by OMP that overpowered the antioxidant defenses of the kidney, resulting in increased vascular resistance and tissue damage [46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…After intravenous heparinization (300 U), cardiac arrest was induced by opening the chest. The cessation of the heart beat was observed within 3–5 min, and donor animals were kept for 40 min on a 37 degree pad [14,15]. The left kidney then was removed with the left renal artery and a short aortic segment, and the left renal vein with a patch of the vena cava.…”
Section: Methodsmentioning
confidence: 99%